2015
DOI: 10.1590/1413-81232015202.01212014
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de competências de Agentes Comunitários de Saúde para coleta de dados epidemiológicos

Abstract: Avaliação de competências de Agentes Comunitários de Saúde para coleta de dados epidemiológicosAssessment of competencies of community health workers for epidemiological data collection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
3
6
0
7
Order By: Relevance
“…The socioeconomic profile of Community Health Workers of this study was similar to that found in other regions of Brazil (7)(8)(9) and countries, such as India (10) and Kenya, (11) being characterized by women, married, with over 12 years of education in young adult age group. These data reflect the participation of women in the labor market, allowing greater family income and women's social advancement and performance, instinctively, the caregiver role in society and community resistance to the Community Health Worker male, due to embarrassment of families in revealing specificities.…”
Section: Discussionsupporting
confidence: 82%
“…The socioeconomic profile of Community Health Workers of this study was similar to that found in other regions of Brazil (7)(8)(9) and countries, such as India (10) and Kenya, (11) being characterized by women, married, with over 12 years of education in young adult age group. These data reflect the participation of women in the labor market, allowing greater family income and women's social advancement and performance, instinctively, the caregiver role in society and community resistance to the Community Health Worker male, due to embarrassment of families in revealing specificities.…”
Section: Discussionsupporting
confidence: 82%
“…A survey 38 that evaluated CHWs' schooling level found an increased level of schooling in this professional category, which can be noted considering that about 45% of individuals studied have a professional schooling level. An interesting result was that, among those who reported having completed higher education, the most prevalent courses did not belong to the health sector, and as described by Musse et al 33 , human and social areas' courses predominated. This construction shows a trend towards humanistic education among these professionals, which could indicate their potential to articulate policies of a social and economic nature 33 and/ or work temporarily as CHWs as an employment opportunity 35 .…”
Section: Discussionmentioning
confidence: 77%
“…The results of this study conducted through the collection of primary data, with approximately all the CHWs operating in the urban area of a medium-sized city in the southern region of the country bring relevant inputs to be considered in the implementation of CHWs' activities and their primary care actions, in Brazilian municipalities with characteristics similar to Pelotas, Rio Grande do Sul. The studied population consisted almost exclusively of women, as well as in research with the same professionals, in which females represented more than 80% of the samples evaluated [33][34][35] , possibly due to the historical aspects of 34 and Ferraz and Aerts 37 , who demonstrated a higher prevalence of CHWs with 9-11 years of schooling. A survey 38 that evaluated CHWs' schooling level found an increased level of schooling in this professional category, which can be noted considering that about 45% of individuals studied have a professional schooling level.…”
Section: Discussionmentioning
confidence: 99%
“…The status of single or non-established family is usually associated with being younger and having more time to devote to studies and work 13 . Regarding marital status, it is worth mentioning the permanence of the patterns established by the patriarchal society, in which the woman behaves and behaves related to the care, either with the children or even with the other members of the family.…”
Section: Socio-demographic Profile Of Participantsmentioning
confidence: 99%
“…Research reveals that most CHAs have a high school education level and half of them have been working for more than five years in this profession, predominantly in the urban area, which may influence access to higher education, which has been found to be 32 , 2% of participants started or finished 3 rd grade 13 . Based on these indicators, in general, the sample analyzed in the present study converges with the recommendations of the Ministry of Health for the work of these workers, who must have resided for at least two years in the working community; Be at least eighteen years old, able to read, write and have full-time availability to carry out their activities 15 .…”
Section: Socio-demographic Profile Of Participantsmentioning
confidence: 99%